What is the evidence for the role of TRP channels in inflammatory and immune cells?. (18th February 2016) - Parenti, A; De Logu, F; Geppetti, P; Benemei, S
Abstract : A complex network of many interacting mechanisms orchestrates immune and inflammatory responses. Among these, the cation channels of the transient receptor potential (TRP) family expressed by resident tissue cells, inflammatory and immune cells and distinct subsets of primary sensory neurons, have emerged as a novel and interrelated system to detect and respond to harmful agents. TRP channels, by means of their direct effect on the intracellular levels of cations and/or through the indirect modulation of a large series of intracellular pathways, orchestrate a range of cellular processes, such as cytokine production, cell differentiation and cytotoxicity. The contribution of TRP channels to the transition of inflammation and immune responses from a defensive early response to a chronic and pathological condition is also emerging as a possible underlying mechanism in various diseases. This review discusses the roles of TRP channels in inflammatory and immune cell function and provides an overview of the effects of inflammatory and immune TRP channels on the pathogenesis of human diseases.